Magnetic metallomesogenic complexes of Cu(ii), Ni(ii), Co(ii), and Mn(ii) with cyclam and substituted arylcarboxylates / Naima Sharmin - Naima, Sharmin (2016)
The objectives of this research were to synthesise and characterize metal(II) complexes with 1,4,8,11-tetraazacyclotetradecane (cyclam) and substituted arylcarboxylates, and to study their magnetic and mesogenic properties. The ligands were 4-CH3(CH2)15OC5H5N, 4-CH3(CH2)nOC6H4COO- (n = 9, 11, 13, 15) and cyclam. To form metallomesogenic complexes, the mononuclear Cu(II)-cyclam complexes of 4-XC6H4COO- (X = F, Cl, Br, I, NO2) obtained were reacted with 4-hexadecyloxypyridine. Finally, the dinuclear M(II) complexes of 4-CH3(CH2)nOC6H4COO- (M = Cu(II), Ni(II), Co(II) and Mn(II); n = 9, 11, 13, 15) were reacted with cyclam to form stable mononuclear magnetic metallomesogenic complexes. A total of 21 complexes were synthesized and their structural formulae were deduced either by single crystal XRD (for crystals) or by combined instrumental data from elemental analyses, FTIR spectroscopy and UV-vis spectroscopy. Their magnetic properties were determined as room-temperature magnetic susceptibility by the Gouy method, and their thermal and mesomorphic properties were studied by thermogravimetry (TGA), differential scanning calorimetry (DSC), and polarizing optical microscopy (POM). The organic ligands were also characterized by 1H-NMR spectroscopy. All complexes have octahedral M(II) centres, paramagnetic and thermally stable. The thermal stabilities of [Cu(cyclam)(L)2](4-XC6H4COO)2.2H2O (Tdec = 200 - 226 °C) were lower than [Cu(cyclam)(H2O)2](R)2, [M(cyclam)(R)2].2H2O, and [Mn(cyclam)(R)2]R.2H2O (M = Ni, Co; R = 4-CH3(CH2)nOC6H4COO; n = 9, 11, 13, 15; Tdec = 229 – 286 °C). All complexes, except for [Cu(cyclam)(L)2] (4-NO2C6H4COO)2.2H2O, exhibited mesomorphism.